The Oasis papers 9 : a tribute to Anthony J. Mills after forty years of research in Dakhleh Oasis : proceedings of the ninth International Conference of the Dakhleh Oasis Project - Bowen, Gillian E.; Bowen, Gillian E.; Hope, Colin; Hope, Colin (Monograph / Dakhleh Oasis Project, 2019)
This new volume in the Oasis Papers series marks the 40th anniversary of archaeological fieldwork in the Dakhleh Oasis in Egypt's Western Desert under the leadership of Anthony J. Mills and presents a synthesis of the current state of our knowledge of the oasis and its interconnections with surrounding regions, especially the Nile Valley. The papers are by distinguished authorities in the field and postgraduate students who specialise in different aspects of Dakhleh and presents an almost complete survey of the archaeology of Dakhleh including much unpublished, original material. It will be one of the few to document a specific part of modern Egypt in such detail and thus should have a broad and lasting appeal. The content of some of the papers is unlikely to be published in any other form elsewhere. Dakhleh is possibly the most intensively examined wider geographic region within Egypt